ChemInform Abstract: Towards Supramolecular Catalysis with Small Self‐Assembled Peptides. Issue 36 (September 2015) - Singh, Nishant; Tena‐Solsona, Marta; Miravet, Juan F.; Escuder, Beatriu
Abstract Review: [52 refs.